2014
DOI: 10.1139/cjpp-2013-0503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bone-marrow-derived mesenchymal stem cells on adriamycin-induced chronic nephropathy

Abstract: administration of BM-MSCs during induction of ADR nephropathy provides partial protection, which could be due to improvements in the levels of of endogenous antioxidants, reduction of apoptosis, and maintenance of the integrity of the glomerular membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
6
17
1
Order By: Relevance
“…In this meta-analysis, four studies [16,18,22,26] were included for the assessment of MDA, four [16,18,22,26] for GSH, three [10,16,22] Table 2).…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In this meta-analysis, four studies [16,18,22,26] were included for the assessment of MDA, four [16,18,22,26] for GSH, three [10,16,22] Table 2).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Four studies [16,23,26,34] for inflammatory cells, two studies [16,26] for necrotic tubule, two studies [16,26] for regenerative tubules and three studies [16,26,34] Table 2).…”
Section: Assessment Of Renal Pathologymentioning
confidence: 99%
“…In this meta-analysis, four studies [16,18,22,26] were included for the assessment of MDA, four [16,18,22,26] for GSH, three [10,16,22] for SOD. The results indicated that the difference between MSCs treatment group and control group was notable for MDA, GSH, SOD (MDA: WMD=-17.21, 95%CI: -20.38, -14.04, P < 0.00001; GSH: WMD = 4.62, 95%CI: 2.74, 6.50, P < 0.00001; SOD: WMD = 5.42, 95%CI: 2.92, 7.93, P < 0.0001; Table 2).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Four studies [16,23,26,34] for in ammatory cells, two studies [16,26] for necrotic tubule, two studies [16,26] for regenerative tubules and three studies [16,26,34] Table 2).…”
Section: Assessment Of Renal Pathologymentioning
confidence: 99%
“…Sections (4-μm-thick) cut from 10% formalin-fixed, paraffin-embedded kidney samples were stained with Hematoxylin and Eosin (H&E) and Masson Trichrome staining, for evaluation of renal glomerular damage, tubulo-interstitial damage (Cao et al, 2000) and degree of fibrosis (Sarhan et al, 2014).…”
Section: Renal Histopathological Examinationmentioning
confidence: 99%